The Effect of Head Nurse’s Supervision on the Implementation of Effective Communication (SBAR) During The Handover Process - Miming Oxyandi; Khoirin (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: The Situation, Background, Assessment And Recommendation (SBAR) method was very effective in increasing the effectiveness of Handover process between shifts or between staff in the same or different clinical areas. The SBAR method was used when nurses carried out the handovers, moved the treatment rooms and reported the patient's condition to the doctor. One of the factors that influenced the implementation of the effectiveness of SBAR communication was the role of room head supervision as a form of learning guidance, sharing experiences, providing motivation and counseling. Objectives: To determine the effect of head nurse’s supervision on the implementation of effective communication (sbar) during the handover process. Methods: This study used a qualitative approach with the Pre-Experimental Experiment method, while the research design was One Grup Design pre-intervention - post-intervention. This research was conducted at a private hospital in Palembang. The data normality test was carried out by using the Kolmogorov-Smirnov statistical test, while the bivariate analysis used a non-parametric statistical test, namely the Wilxocom test. Results: The results of the study on the implementation of SBAR effective communication showed the results before intervention as much as 100.0% in the poor category, while after the intervention treatment as many as 60.0% in the perfect category. Based on the Wilcoxon signed rank statistical test, the Z value was -3.411 and the asymp sig value. (2-tailed) 0.001 is smaller than the alpha level 5% (0.05) so that Ho was rejected; there is a significant average difference before and after the supervision of the head of the room on the implementation of SBAR effective communication. Suggestion: It is expected to improve the implementation of SBAR effective communication at the time of Handover which is more optimal, especially in the room by resocializing SPO, optimizing the supervision of the head of the room and continuing to attend training, especially on Effective SBAR communication.